2011
DOI: 10.1038/pr.2011.847
|View full text |Cite
|
Sign up to set email alerts
|

Are Low Birth Weight Infants at Risk for Mineral Disturbance in Early Neonatal Period?

Abstract: Bacground and aims:The physiological levels of calcium and magnesium are very unstable in the first few days after birth, due to abrupt interruption of placental supply, low level of PTH and high levels of calcitonin, physiological acidosis. Infants with intrauterine growth retardation and preterm birth are at risk for hypocalcemia or hypomagnesemia. Often asymptomatic they can be undiscovered and untreated. There are a lot of controversies in regards with the physiological low limit of calcium and magnesium; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Hypocalcemia is often asymptomatic may remain undiscovered and untreated. 16 Blaga et al in 2011 found that 16% of term IUGR neonates presented with hypocalcemia. 16 An Indian study found that 10% of the cases, which consisted of 200 term IUGR infants had hypocalcemia in comparison to 4% of the normal control population.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Hypocalcemia is often asymptomatic may remain undiscovered and untreated. 16 Blaga et al in 2011 found that 16% of term IUGR neonates presented with hypocalcemia. 16 An Indian study found that 10% of the cases, which consisted of 200 term IUGR infants had hypocalcemia in comparison to 4% of the normal control population.…”
Section: Discussionmentioning
confidence: 98%
“…16 Blaga et al in 2011 found that 16% of term IUGR neonates presented with hypocalcemia. 16 An Indian study found that 10% of the cases, which consisted of 200 term IUGR infants had hypocalcemia in comparison to 4% of the normal control population. 17 Mazumder et al also correlated serum calcium with growth retarded neonates, in this study, 9.4% of the term IUGR babies had hypocalcemia versus 6.2% among term AGA babies.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation